Hellenic Temples and Christian Churches : a Concise History of the Religious Cultures of Greece from Antiquity to the Present. - Makrides, Vasilios, 1961- (NYU Press, 2009)
"Covering an expanse of more than three thousand years, Hellenic Temples and Christian Churches charts, in one concise volume, the history of Greece's religious cultures from antiquity all the way through to present, post-independence Greece. Focusing on the encounter and interaction between Hellenism and (Orthodox) Christianity, which is the most salient feature of Greece's religious landscape--influencing not only Greek religious history, but Greek culture and history as a whole--Vasilios N. Makrides considers the religious cultures of Greece both historically, from the ancient Greek through the Byzantine and the Ottoman periods up to the present, and systematically, by locating common characteristics and trajectories across time. Weaving other traditions including Judaism and Islam into his account, Makrides highlights the patterns of development, continuity, and change that have characterized the country's long and unique religious history."--Publisher's description.